Naringenin Regulates FKBP4/NR3C1/NRF2 Axis in Autophagy and Proliferation of Breast Cancer and Differentiation and Maturation of Dendritic Cell - Xiong, Hanchu; Chen, Zihan; Lin, Baihua; Xie, Bojian; Liu, Xiaozhen; Chen, Cong; Li, Zhaoqing; Jia, Yunlu; Wu, Zhuazhua; Yang, Min; Jia, Yongshi; Wang, Linbo; et al. (Frontiers in Immunology, 2022)
TMEM173 is a pattern recognition receptor detecting cytoplasmic nucleic acids and transmits cGAS related signals that activate host innate immune responses. It has also been found to be involved in tumor immunity and tumorigenesis. In this study, we firstly identified that FKBP4/NR3C1 axis was a novel negative regulator of TMEM173 in human breast cancer (BC) cells. The effect of FKBP4 appeared to be at the transcriptional level of TMEM173 since it could suppress the promoter activity of TMEM173, thereby affecting TMEM173 at mRNA and protein levels. Bioinformatics analysis and in vitro experiments further demonstrated that FKBP4 regulated TMEM173 via regulating nuclear translocation of NR3C1. We then reported that naringenin, a flavonoid, widely distributed in citrus and tomato, could enhance autophagy and suppress proliferation of BC cells through the induction of TMEM173 in vitro and in vivo. Naringenin was also found to promote tumor-infiltrating dendritic cell (TIDC) maturation through FKBP4/NR3C1/TMEM173 axis of both BC cells exosome and DC itself. Our study found an unprecedented strategy used by BC to escape from TMEM173 mediated tumor suppression. We demonstrated that naringenin could induce cell proliferation inhibition and cytoprotective autophagy of BC cells and enhance TIDC maturation, at least in part, though regulation of FKBP4/NR3C1/TMEM173 signaling pathway. Identification of FKBP4/NR3C1 axis as a novel TMEM173 regulator would provide insights for novel anti-tumor strategy against BC among tumor microenvironment.